2015
DOI: 10.1142/s1793545815300050
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy in the treatment of intracranial gliomas: A review of current practice and considerations for future clinical directions

Abstract: Invasive grade III and IV malignant gliomas remain di±cult to treat with a typical survival time post-diagnosis hovering around 16 months with only minor extension thereof seen in the past decade, whereas some improvements have been obtained towards¯ve-year survival rates for which completeness of resection is a prerequisite. Optical techniques such as°uorescence guided resection (FGR) and photodynamic therapy (PDT) are promising adjuvant techniques to increase the tumor volume reduction fraction. PDT has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 119 publications
0
15
0
Order By: Relevance
“…1,2 A considerable number of clinical trials have been conducted with some very promising results for hematoporphyrin derivative, 3 aminolevulinic acid (ALA)-protoporphyrin IX (PPIX), 4,5 and talaporfin 6 mediated PDT. 1,2 A considerable number of clinical trials have been conducted with some very promising results for hematoporphyrin derivative, 3 aminolevulinic acid (ALA)-protoporphyrin IX (PPIX), 4,5 and talaporfin 6 mediated PDT.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 A considerable number of clinical trials have been conducted with some very promising results for hematoporphyrin derivative, 3 aminolevulinic acid (ALA)-protoporphyrin IX (PPIX), 4,5 and talaporfin 6 mediated PDT. 1,2 A considerable number of clinical trials have been conducted with some very promising results for hematoporphyrin derivative, 3 aminolevulinic acid (ALA)-protoporphyrin IX (PPIX), 4,5 and talaporfin 6 mediated PDT.…”
Section: Introductionmentioning
confidence: 99%
“…Most photosensitizing agents are injected intravenously, with the therapeutic light applied directly to the tumor resection bed. 51,52 Studies have shown that topical application of photosensitizing agents, such as in dermatologic applications, is also effective. 34 Fluid-filled balloons that distribute the light to the cavity walls have been studied to evenly distribute the therapeutic light throughout.…”
Section: Discussionmentioning
confidence: 99%
“…The results clearly show the correlation between the bioluminescence-based PDT response and the volume-averaged Since PDT is inevitably subject to intrinsic cancer resistance at the cellular and molecular levels via drug e®lux, hypoxia, levels of pigmentation and repair mechanisms, Huang et al in Fuzhou, China review the recent progress in understanding the interaction between multidrug resistance (MDR) transporters and PS uptake. 6 In addition, emerging strategies are discussed to overcome such resistance, including the use of MDR transport inhibitors, anti-vascular PDT, photochemical internalization, intratumoral injection of PS, multifunctional PS nanocarriers and enhancing the antitumor immunity. These strategies aim to make anticancer PDT more e®ective in the clinic and so gain greater acceptance into mainstream medicine.…”
Section: Published 29 December 2014mentioning
confidence: 99%